2009
DOI: 10.1590/s0100-40422009000900020
|View full text |Cite
|
Sign up to set email alerts
|

Influence of basic properties of Mg,Al-mixed oxides on their catalytic activity in knoevenagel condensation between benzaldehyde and phenylsulfonylacetonitrile

Abstract: The catalytic performance of Mg,Al-mixed oxides (MO20, MO25 and MO33) derived from hydrotalcites was evaluated in the Knoevenagel reaction between benzaldehyde and phenylsulfonylacetonitrile at 373 and 383 K. The best results were obtained for the sample MO20 that presented the highest basic sites density and external area and the smallest crystallite sizes. The relative amount of basic sites with weak to intermediate strength also played an important role on catalytic performance. By increasing the catalyst c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 37 publications
(62 reference statements)
1
11
0
1
Order By: Relevance
“…In this case, it is also associated with the temperature of catalyst pre-treatment (450 °C), but previously we observed the same results for Mg-Al mixed oxides pre-treated at higher temperature [19]. Total concentration of basic sites (CBS) was calculated as the total amount of CO 2 desorbed between 0 and 475 °C (Table 1) [29][30][31][32]. It is clearly seen that the intensity of desorption peak (concentration of basic sites) decreased with increasing Mg/Al molar ratio.…”
Section: Amount Of Basic Sitessupporting
confidence: 56%
See 1 more Smart Citation
“…In this case, it is also associated with the temperature of catalyst pre-treatment (450 °C), but previously we observed the same results for Mg-Al mixed oxides pre-treated at higher temperature [19]. Total concentration of basic sites (CBS) was calculated as the total amount of CO 2 desorbed between 0 and 475 °C (Table 1) [29][30][31][32]. It is clearly seen that the intensity of desorption peak (concentration of basic sites) decreased with increasing Mg/Al molar ratio.…”
Section: Amount Of Basic Sitessupporting
confidence: 56%
“…CO 2 desorption peak was observed between 0 and 475 °C. This peak could be attributed to desorption of CO 2 from weak, medium and strong basic sites [29][30][31][32]. Another peak was observed above 475 °C (not shown in the figure) that have been attributed to desorption of CO 2 from the residual amorphous MgCO 3 phase that was not decomposed during the hydrotalcite thermal pre-treatment [33].…”
Section: Structure and Composition Of Hydrotalcite And Mg-al Mixed Oxmentioning
confidence: 91%
“…Actually, as shown by Ordóñez et al ., the substitution of Al 3+ by Fe 3+ in the structure of the resulting mixed oxide leads to a slight decrease in the concentration of basic sites and a more marked decrease in the concentration of acid sites. According to other studies, the acid sites are related to the presence of tetrahedrally coordinated Me 3+ ions in the crystalline structure. In the parent structure, Me 3+ ions are usually coordinated octahedrally.…”
Section: Resultsmentioning
confidence: 84%
“…8,9 Nevertheless, the influence of the chemical composition of Mg−Al mixed oxides on the amount and the strength of their basic/acid sites as well as their catalytic performance is still a matter of discussion. 4,5,10,11 Considering the performance of Mg−Al mixed oxides in the condensation reactions, authors have generally reported that the activity increases with increasing both the total number of basic sites and their density. 5,10,11 In contrast, some authors 4 did not observe any clear relation between the activity and the basicity of Mg−Al mixed oxide.…”
Section: Synthetic Mg−al Hydrotalcites Have Chemical Compositions [M 2+mentioning
confidence: 99%